An Anglican View of the Papacy Post-Vatican II. Issue 1 (16th February 2015) - Platten, Stephen
Abstract: This article provides a current view of Anglican attitudes to the Papacy. First of all historical background is examined in relation to mutual perceptions of Anglicanism and Roman Catholicism going back to the early church and then moving forward through the Reformation to the twentieth century. The period from 1966 onwards saw the visit of Geoffrey Fisher to Pope John XXIII which began to change perceptions. The establishment of the Anglican Centre in Rome in 1966 was a crucial development. The setting up of the Anglican Roman Catholic International Commission, following the Malta Report in 1966 altered perceptions and understandings of Anglican and Roman Catholics mutually. There is still a variety of Anglican reactions to the Papacy.